Statistical screening and optimization of factors influence lipase production from palm kernel cake using Candida Cylindracea by solid-state bioconversion - Elgharbawy, Amal A.M.; Alam, Md. Zahangir; Hamzah, Mohd. Salleh (2013)
Several factors affecting lipase production by Candida cylindracea were studied using palm kernel cake (PKC) as the basal medium. The factors included for media components: peptone, yeast extract, glucose, NaNO3, MgSO4, olive oil and Tween-80 and process conditions: inoculum, temperature, pH and moisture content. Using Plackett–Burman (PB) design for screening, the highest lipase activity obtained was 9.41 U/ml in the absence of glucose, peptone and MgSO4. The factors that contributed the most in lipase production were further investigated using one-factor-at- a-time (OFAT) experiments in order to find the optimal conditions for the lipase productivity. An activity of 30.0 U/ml was obtained after 144h of fermentation by the end of this study which was used for optimization afterword.